THE ACCELERATED STABILITY STUDY OF CONSTALAX CHURNA- AN AYURVEDIC FORMULATION - B. Bhagwat, Gajanan; S Kadam, *Swapna; Hivarale, Madhuri (International Journal of Ayurveda and Pharma Research, 2017)
Constalax churna, greenish brown powder with characteristic odor and bitter salty taste was evaluated for its stability, as per ICH guidelines Q1A (R2) at accelerated conditions (Temperature: 40 °C ± 2, Relative Humidity : 75% ± 5). The real time stability is estimated at temperature: 25 °C ± 2 &relative humidity 60% ± 5.The study sample was observed for changes in different parameters like physico-chemical, organoleptic and microbial load for 6 month under accelerated conditions and for real time stability study observed for one year. Real time stability was comparatively estimated to evaluate actual degradation rate of Constalax Churna with respect to accelerated conditions. Up to six months of storage at accelerated condition, no change was observed in organoleptic parameters like colour, odour and taste of Constalax Churna. Changes in of different physico-chemical parameters were taken into account to evaluate intercept and slope. Extrapolated shelf life of Constalax Churna was calculated with 10% degradation rate from physico-chemical parameters at accelerated condition 40 °C ± 2 and 75% ± 5 RH. The present evaluation supports that the Constalax Churna was appropriate at accelerated condition up to 6 month storage. From this accelerated stability study it could be extrapolated that shelf life of Constalax Churna is 25.42 months (2.11years) for climatic zone I & II countries. Real time stability data of Constalax Churna showed very good stability up to 2 years.